Factors that affect the adoption of internet banking in Malaysia - Ong, Tze San; Hong, Yong Hoe; Teh, Boon Heng; Soh, Patrick Chin Hooi; Tan, Chun Ping (Medwell Journals, 2014)
This study identifies factors that induce consumers to adopt internet banking services. It analyses data from 200 respondents in Malaysia. The findings show that cost saving, risk and privacy, features availability and convenience are the key factors that influence consumers’ internet banking usage. These findings should encourage banks to improve their internet banking systems and implement them in a more user-friendly way in order to increase the level of adoption of internet banking by consumers.